Food image and satisfaction: the case of Negeri Sembilan heritage food - Fakhıra, Nuraına; Md Sawari, Siti Salwa (2021)
Food heritage has been recognized as a tool for regional growth, enhancing local production through backward ties in the supply chain of tourism partnerships. It is an essential aspect of sustainable tourism. The importance of food as a determinant of the image of the destination was presented in several studies. Food heritage is one of the elements of the destination's image and the importance of developing the destination's attractiveness. This article aims to investigate the relationship between Negeri Sembilan heritage food image and tourist satisfaction. The pilot survey was run on a total of 30 domestic tourists that had experiences in consuming heritage food in Negeri Sembilan. The finding in this research discovers that there is no relationship between food image and satisfaction. Research on this subject can provide up-to-date information on updated issues and recommendations in this area, contributing to the study on heritage food tourism.